Sales forecasting management a demand management approach - Mentzer, John T.
Mentzer and Moon apply their 25 years of sales forecasting management research to their techniques for sales forecasting. They cover managing the process, performance measurement regression analysis, qualitative sales forecasting, and forecasting systems. The second edition has been reorganized and includes new insights on qualitative forecasting,